2010
DOI: 10.1007/s10545-010-9251-y
|View full text |Cite
|
Sign up to set email alerts
|

Danon disease: intrafamilial phenotypic variability related to a novel LAMP‐2 mutation

Abstract: Danon disease is an X-linked lysosomal disorder, characterized by hypertrophic cardiomyopathy, skeletal myopathy and mental retardation. We report a family with a novel mutation, in which the mother and her three sons were affected with various clinical presentations. A massive hypertrophy of the left ventricle was the predominant feature in the three male patients, with different degrees of severity of cardiac symptoms, from isolated palpitations to cardiac failure and sudden death. Muscle pain and weakness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Maron et al 9 reported that six of seven Danon disease patients were boys with a median age of 14 years, and six patients were with WPW syndrome and deeply inverted T-waves at diagnosis. Furthermore, all the three patients had markedly elevated serum hepatic enzymes and CK concentrations, consistent with previous studies by Yang et al, 7 Maron et al, 9 Cottinet et al, 10 Balmer et al, 11 and Morisawa et al…”
Section: Discussionsupporting
confidence: 90%
“…Maron et al 9 reported that six of seven Danon disease patients were boys with a median age of 14 years, and six patients were with WPW syndrome and deeply inverted T-waves at diagnosis. Furthermore, all the three patients had markedly elevated serum hepatic enzymes and CK concentrations, consistent with previous studies by Yang et al, 7 Maron et al, 9 Cottinet et al, 10 Balmer et al, 11 and Morisawa et al…”
Section: Discussionsupporting
confidence: 90%
“…In most patients, the first symptoms were heart murmurs , chest pain , palpitations or easy fatigability . Syncopal episodes in young patients were frequent (40% of cases) .…”
Section: Clinical Features In Male Patientsmentioning
confidence: 99%
“…At echocardiography, the cardiomyopathy typically manifested as a concentric LV hypertrophy , with preserved ejection fraction, especially in childhood , but later progressed to a dilated pattern. DCM occurred in 10–33% of cases .…”
Section: Clinical Features In Male Patientsmentioning
confidence: 99%
“…2 Although apparently rare, the geographic distribution of Danon disease is wide, reported from the USA, Italy, Australia, Sweden, the UK, Japan and China. [3][4][5][6][7][8][9][10][11] The pathological hallmark of the disease is intracytoplasmic vacuoles containing autophagic material and glycogen in cardiac ( Figure 1) and skeletal muscle cells. 1, 12 The final diagnosis is based on the genetic analysis of LAMP2 gene.…”
mentioning
confidence: 99%